Identitetna pojmovanja - med lokalnim in globalnim - Medica, Karmen (Monitor ISH, 2004)
Perceptions of identity - between the local and the global. An implicit understanding and interpretation of the identity riddle is becoming a by-product of the recent globalization processes. The paper outlines the current perceptions of this phenomenon, reaching from diverse interpretations by Slovene authors to the recent presentations of Baumann, Castells, or Getinet. The traditional notion of identity has aquired an additional subjective component. The national identity, on the other hand, grows hybrid and dispersed, thus requiring new and partlz unfamiliar patterns of reflection. Modern society is increasingly characterised by the option of no-identity and no-belonging, from the subjectivity of the ethnic identities to the ubiquitous routine of the national identity.
Keywords: identiteta; narodna identiteta; etnična identiteta; nationalism; nacionalizem; nacionalna država